2019
DOI: 10.18502/jovr.v14i3.4780
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pupil Area During Low-energy Femtosecond Laser Assisted Cataract Surgery

Abstract: PurposeTo study the potential changes in pupil area within low-energy femtosecond-laser assisted cataract surgery (FLACS).MethodsA retrospective assessment of the pupil size was performed in the eyes undergoing FLACS using the Ziemer LDV Z8. We measured the pupil diameters as part of the images taken preoperatively and at the completion of laser pretreatment (after releasing the suction). We calculated the pupil area in 40 eyes of 40 patients (14 right and 26 left eyes). The mean ± standard deviation (SD) of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
17
3
Order By: Relevance
“…Apparently, the low energy Z8 laser would induce minimal collateral damage to surrounding tissue, thus ensuing lower amounts of prostaglandin release, thereby reducing the risk of pupillary miosis during the surgery 32 , compared with high energy laser systems 31 , 33 , 35 , 36 . In agreement with these findings, a recent study reported no significant changes in pre- and post-laser treated pupil area with low energy Z8 FLACS system 37 . Conversely, Diakonis et al revealed significant pupillary miosis with 3 different high energy femtosecond laser platforms 38 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Apparently, the low energy Z8 laser would induce minimal collateral damage to surrounding tissue, thus ensuing lower amounts of prostaglandin release, thereby reducing the risk of pupillary miosis during the surgery 32 , compared with high energy laser systems 31 , 33 , 35 , 36 . In agreement with these findings, a recent study reported no significant changes in pre- and post-laser treated pupil area with low energy Z8 FLACS system 37 . Conversely, Diakonis et al revealed significant pupillary miosis with 3 different high energy femtosecond laser platforms 38 .…”
Section: Discussionsupporting
confidence: 80%
“…Given the lower incidence of intraoperative miosis in the Z8 group, patients with documented NSAID allergy may benefit from the use of the low energy Z8 laser. The hypothesis is supported by the findings of Mirshahi et al, that did not detect statistically significant changes in the pupil area after laser pre-treatment with the low energy FEMTO LDV Z8 37 .…”
Section: Discussionmentioning
confidence: 60%
“…19,27 Intraoperative miosis of the pupil observed in some studies following pretreatment with the FL has also been attributed to increased prostaglandin levels after laser treatment. 28,32 Constricted pupils may increase surgical manipulation during phacoemulsification. Correspondingly, some studies have found a trend of higher risk of PCME development following FLACS compared with manual phacoemulsification.…”
Section: Dovepressmentioning
confidence: 99%
“…38 Correspondingly, less pupil constriction with the use of low-energy FLs has been attributed to less release of prostaglandins. 28,33 Therefore, it can be postulated that low-energy laser platforms may induce low inflammation due to laser pretreatment.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation